Kampania propagandowa w sprawie orędzia biskupów polskich do biskupów niemieckich z 1965 roku w świetle prasy z Wrocławia i Zielonej Góry = Propaganda campaign on the letter of reconciliation of the polish bishops to the german bishops as of 1965 in the light of Wrocław's and Zielona Góra's news media - Krzyżanowski, Sławomir (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article is devoted to a significant event, namely the creation of the memorable Letter of Reconciliation of the Polish Bishops to the German Bishops as of 18 November 1965. This fact undoubtedly contributed to the breach of the deadlock in the Polish German relationship following the Second World War.
Keywords: prasa zielonogórska; prasa wrocławska; list biskupów polskich do biskupów niemieckich; Polska - historia - 19 - 20 w.